Supporting Faculty at all Levels through the GROWTH Mentoring Program - Yojanna Cuenca-Carlino; Stacey Jones Bock; Tara Kaczorowski (Academic Chairpersons Conference Proceedings, 2019)
Presenters will share the process of developing a cross-mentoring program designed to support faculty in teaching and scholarship. The program provided professional development through workshops and peer-mentoring in teaching through the use of video analysis. Presenters will discuss empirical results, lessons learned, and recommendations for replication in other institutions.
Keywords: faculty; mentoring; departmental culture; video analysis